The seal woman - Farmer, Beverley (St Lucia, Queensland : University of Queensland Press, 1992)
In mourning for her husband lost at sea, Dagmar leaves the wintry landscapes of the Northern Arctic region for the tranquility of Swanhaven and a healing Australian summer.
Keywords: Widows -- Fiction; Women -- Australia -- Fiction; Psychological fiction